Rett Syndrome: Crossing the Threshold to Clinical Translation - Katz, David M.; Bird, Adrian; Coenraads, Monica; Gray, Steven J.; Menon, Debashish U.; Philpot, Benjamin D.; Tarquinio, Daniel C. (Trends in neurosciences (Regular ed.), 2016)
Lying at the intersection between neurobiology and epigenetics, Rett syndrome (RTT) has garnered intense interest in recent years, not only from a broad range of academic scientists, but also from the pharmaceutical and biotechnology industries. In addition to the critical need for treatments for this devastating disorder, optimism for developing RTT treatments derives from a unique convergence of factors, including a known monogenic cause, reversibility of symptoms in preclinical models, a strong clinical research infrastructure highlighted by an NIH-funded natural history study and well-established clinics with significant patient populations. Here, we review recent advances in understanding the biology of RTT, particularly promising preclinical findings, lessons from past clinical trials, and critical elements of trial design for rare disorders. Studies of RTT mouse models have convincingly demonstrated that neurological disability caused by loss of methyl-CpG-binding protein 2 (MeCP2) function is reversible to a significant degree. Recent insights into the biology of MeCP2 and its role in regulating interactions between DNA and repressor protein complexes seemed poised to resolve longstanding controversies about the role of MeCP2 in transcriptional control. The knowledge that reintroduction of Mecp2 can restore circuit functionality in mouse models of RTT has spurred the investigation of gene replacement and gene reactivation strategies as comprehensive and potentially transformative treatment approaches for RTT. Pharmacologic strategies targeting neurotransmitter and neuronal growth factor signaling pathways have proven highly effective at improving neurological function in mouse models of RTT. The natural history of RTT is becoming increasingly well defined, facilitating the identification of clinically measurable endpoints for therapeutic trials.